Forage tree species of the Yucatan Peninsula: an option to diversify agroecosystems - Casanova-Lugo, Fernando; Gutiérrez-López, Ana; Jiménez-Hernández, Hector Manuel; Quezada-Raya, Guadalupe; Enríquez-Nolasco, Justo Ramón; Cetzal-Ix, William Rolando (Ecosistemas y Recursos Agropecuarios, 2025)
The objective of this study was to identify the forage tree species (FTS) present in the Yucatan Peninsula (YP), to document their uses and contribution to agrobiodiversity and regional food security. With an exhaustive bibliographic review, the forage species present were integrated and updated and their uses and associated benefits were classified; Through studies of the flora of the YP and the list of trees of the Mayab, the biogeographic origin and growth forms of the species were determined. Descriptive analyzes were carried out on the information obtained with the Origin Pro® 2023b software. A total of 518 species of flora with various uses (16 categories) were recorded, of which 82 are FTS. In addition, they have other uses such as firewood, medicines, crafts and wood with 59, 56, 46 and 45 species, respectively. The FTS come from 27 botanical families, the most important being Fabaceae, which represents 40% of the species. Regarding botanical origin, 64% of FTS are native. Each species presents at least two forms of use, which indicates its relevance in the local economy and its potential use for animal feed. However, to fully take advantage of these resources, it is crucial to document the nutritional composition and promote sustainable practices for their forage use for livestock producers in the YP.